Psoriasis : coping with social stigma - Magdoline, Luhok (Universiti Malaysia Sarawak, (UNIMAS), 2010)
It aimed in exploring the experience of being stigmatized, describing the coping strategies used and if effectiveness in dealing with social stigma. With in-depth interview to nine participants in this qualitative research.